2008
DOI: 10.1007/s00468-008-0295-7
|View full text |Cite
|
Sign up to set email alerts
|

Leaf structure of the cerrado (Brazilian savanna) woody plants

Abstract: With the aim of recognizing the commonest leaf pattern found in the woody flora of the cerrado (the Brazilian savanna) we analyzed the leaf anatomy of 30 representative species. The leaves are mostly dorsiventral and hypostomatic and covered by trichomes and a thick layer of wax and cuticle; the vascular bundles are surrounded by a sheath of fibers. The mesophyll has a developed palisade tissue, dispersed sclerified cells and idioblasts bearing crystals and phenolic compounds. We compared the results with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 33 publications
5
47
0
9
Order By: Relevance
“…The cuticle is a hydrophobic structure responsible for cuticular transpiration reduction and for nutrient leaching. It also protects the leaf from the wind and from fungal invasion (Turner 1994); it gets thicker as the ambient light intensity increases, as it was noticed by Bieras and Sajo (2009) in their anatomical studies on Cerrado species. A study performed by Martinez and Medri (1985) found that the cuticle is thicker in the leaves located at the upper extracts, in which they are more exposed to light.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The cuticle is a hydrophobic structure responsible for cuticular transpiration reduction and for nutrient leaching. It also protects the leaf from the wind and from fungal invasion (Turner 1994); it gets thicker as the ambient light intensity increases, as it was noticed by Bieras and Sajo (2009) in their anatomical studies on Cerrado species. A study performed by Martinez and Medri (1985) found that the cuticle is thicker in the leaves located at the upper extracts, in which they are more exposed to light.…”
Section: Discussionmentioning
confidence: 82%
“…This adaptation process occurs through the optimization of the gas exchange between water loss -through transpiration -and CO 2 absorption, which is necessary for photosynthesis. Several studies, such as those conducted by Bieras and Sajo (2009) and Rossatto (2011), have demonstrated that the epidermis modification is distinct in different species, especially regarding changes in radiation levels. The stomata are extremely important in anatomical studies involving different environments and radiation levels, since the increased stomatal frequency in leaves exposed to high irradiance may be an important adaptive mechanisms in drier environments (Abrams and Mostoller 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the tree (G. polymorpha) had a greater number of sclerophyllous leaf traits, which are normally reported for woody, "Cerrado" species. These traits include smaller and thicker leaves, well developed parenchyma (Bieras & Sajo 2009), high stomatal density (Rossatto et al 2009a), higher photosynthetic rates (A area ) and lower values of specific leaf area (Rossatto et al 2009b). On the other hand, the shrub (G. barrosii) presented more mesophytic leaf traits, bigger and thinner leaves, higher values of specific leaf area and lower photosynthetic rates (A area ), which are reported for woody species that grow in lower light environments (Sefton et al 2002;Dahlgren et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of stomata on both leaf surfaces can be variable in Asteraceae (Breitwieser 1993;Milan et al 2006). The presence of amphistomatic leaves is variable also among "Cerrado" species (Morretes 1969;Elias et al 2003;Rossatto et al 2009a), despite that the general pattern reported for plants from this vegetation is hypostomatic leaves (Bieras & Sajo 2009). Stomata size was variable and the guard cell length of G. barrosii stomata was shorter.…”
Section: Discussionmentioning
confidence: 99%